PENGARUH AUDITOR SWITCHING, LIKUIDITAS, LEVERAGE, DISCLOSURE DAN FINANCIAL DISTRESS TERHADAP KEMUNGKINAN PENERIMAAN OPINI AUDIT GOING CONCERN - Indri Septiana; Patricia Diana (Jurnal Bina Akuntansi, 2019)
The objective of this study was to obtain empirical evidence about the effect of auditor switching, liquidity, leverage, disclosure and financial distress on the probability of going concern audit opinion. The object of this study is the mining companies listed in Indonesia Stock Exchange in 2013 – 2016. Samples of this research were chosen by using purposive sampling and got 8 mining companies that matched the criteria. The criteria used for choosing the samples are listed on BEI as mining company during period 2013-2016, publish the annual report and audited financial statement in Rupiah, and has a net loss for two periods in a row. This research use regression logistic because the dependent variable measured by nominal scale. The result of this research showed that auditor switching, liquidity, leverage, disclosure and financial distress didn’t have effect to the probability of going concern audit opinion.